(untitled) (UNIHumanitas, 2020)
One of the major shortcomings of Paraguay’s health system is undoubtedly the area of Mental Health, to which barely 1% of the health budget is allocated, highly centralized in the country’s capital, where the only publicly administered psychiatric hospital is located. For the analysis of the current situation of mental health, historical background related to both political and cultural variables must also be considered: on the one hand, 35 years of dictatorship, marked by a hegemonic asylum model that did not allow the implementation of other humanizing systems that influenced the following years of democratic transition; and, on the other hand, stereotypes and stigma related to “mental illness”, prejudices deeply impregnated in the DNA of Paraguayan society.